Structural Insights into High Density Lipoprotein: Old Models and New Facts - Gogonea, Valentin (Frontiers in Pharmacology, 2016)
The physiological link between circulating high density lipoprotein (HDL) levels and cardiovascular disease is well-documented, albeit its intricacies are not well-understood. An improved appreciation of HDL function and overall role in vascular health and disease requires at its foundation a better understanding of the lipoprotein's molecular structure, its formation, and its process of maturation through interactions with various plasma enzymes and cell receptors that intervene along the pathway of reverse cholesterol transport. This review focuses on summarizing recent developments in the field of lipid free apoA-I and HDL structure, with emphasis on new insights revealed by newly published nascent and spherical HDL models constructed by combining low resolution structures obtained from small angle neutron scattering (SANS) with contrast variation and geometrical constraints derived from hydrogen–deuterium exchange (HDX), crosslinking mass spectrometry, electron microscopy, Förster resonance energy transfer, and electron spin resonance. Recently published low resolution structures of nascent and spherical HDL obtained from SANS with contrast variation and isotopic labeling of apolipoprotein A-I (apoA-I) will be critically reviewed and discussed in terms of how they accommodate existing biophysical structural data from alternative approaches. The new low resolution structures revealed and also provided some answers to long standing questions concerning lipid organization and particle maturation of lipoproteins. The review will discuss the merits of newly proposed SANS based all atom models for nascent and spherical HDL, and compare them with accepted models. Finally, naturally occurring and bioengineered mutations in apoA-I, and their impact on HDL phenotype, are reviewed and discuss together with new therapeutics employed for restoring HDL function.